The last of the vamp(ire)s: Two Spanish stories at a semantic fork in the road. Issue 2 (1st October 2019) - Lee Six, Abigail
This article analyses two Spanish vampire stories, 'El señor Cadáver y la señorita Vampiro', by Antonio de Hoyos y Vinent (de Hoyos y Vinent 1919), and La mujer fría, by Carmen de Burgos (de Burgos 1922), in the light of the silent film of 1915, A Fool There Was, which featured Theda Bara in the role of a femme fatale called the 'Vampire'. This screen persona contributed to the popularization of the term vamp for a certain type of predatory woman and the impact of this neologism on writings about vamp(ire)s is explored with reference to the evolution of portrayals of female vampires.